2020
DOI: 10.3390/su12072967
|View full text |Cite
|
Sign up to set email alerts
|

What Should Be Considered when Developing ICT-Integrated Classroom Models for a Developing Country?

Abstract: This study aims to identify factors to be considered when developing Information and Communication Technology (ICT)-integrated classroom models and to suggest a conceptual framework for considering more appropriate classroom models, tailored to the environments and needs of each developing country. In-depth interviews were conducted with experts, yielding many factors to be taken into account when integrating ICT in various educational contexts of developing countries. The factors are categorized into five dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Most researchers also report that the most fundamental and essential aspects are the power source and network connectivity. So the least developed countries are forced to concentrate on building ICT-integrated classrooms in urban environments (Cha et al, 2020).…”
Section: Challenges Of Ict Use In Language Activitiesmentioning
confidence: 99%
“…Most researchers also report that the most fundamental and essential aspects are the power source and network connectivity. So the least developed countries are forced to concentrate on building ICT-integrated classrooms in urban environments (Cha et al, 2020).…”
Section: Challenges Of Ict Use In Language Activitiesmentioning
confidence: 99%
“…The rapid development of technology has compelled tertiary institutions to devise innovative teaching strategies to meet the students' needs and the market's demands. [1][2][3] Covid-19 has forced educational institutions to shift from in-person to online learning. [4][5][6][7] Developing e-learning contents and providing el-learning opportunities is one of the areas advancing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies conducted in Greece (Platinakis,, 2011) show that the obstacles reported by Greek teachers in the Greek High School are similar to those reported in the international literature. Several more studies suggest that the ICT infrastructure available in the classroom has always been essential to effectively embed ICT in teaching and learning (Bariu, 2020;Hyunjin,Taejung and Jongwon, 2020;Lu,Tsai and Wu, 2015;Voogt et al, 2013). However, those studies do not examine the degree to which specific levels of "Resources" may affect ICT integration.…”
Section: Introductionmentioning
confidence: 99%